Evolution of echocardiographic and cardiac magnetic resonance imaging abnormalities during follow-up in patients with multisystem inflammatory syndrome in children. (27th May 2022) - Sirico, D; Basso, A; Sabatino, J; Reffo, E; Cavaliere, A; Biffanti, R; Cerutti, A; Castaldi, B; Zulian, F; Da Dalt, L; Di Salvo, G
Abstract: Aims: Multisystem inflammatory syndrome in children (MIS-C) with cardiovascular manifestations are frequent. However, there is lacking evidence regarding cardiological follow-up of this cohort of patients. The aim of our study was to describe the early and mid-term cardiac abnormalities assessed by standard and speckle-tracking echocardiography (STE), and cardiac MRI (CMR). Methods and results: We enrolled 32 patients (21 male, 11 female), mean age 8.25 ± 4years, with diagnosis of MIS-C. During admission, all children underwent TTE, STE with analysis of left ventricle global longitudinal strain (GLS) and CMR. Patients underwent cardiological evaluation at 2 (T1) and 6 months (T2) after discharge. Cardiac MRI was repeated at 6 months after discharge. Mean left ventricular ejection fraction (LVEF) at baseline was 58.8 ± 10% with 10 patients (31%) below 55%. Speckle-tracking echocardiography showed reduced mean LV GLS (−17.4 ± 4%). On CMR, late gadolinium enhancement (LGE) with non-ischaemic pattern was evident in 8 of 23 patients (35%). Follow-up data showed rapid improvement of LVEF at T1 (62.5 ± 7.5 vs. 58.8 ± 10.6%, P -value 0.044) with only three patients (10%) below ≤ 55% at T1. Left ventricular (LV) GLS remained impaired at T1 (−17.2 ± 2.7 vs.−17.4 ± 4, P -value 0.71) and significantly improved at T2 (−19 ± 2.6% vs. −17.4 ± 4%, P -value 0.009). LV GLS was impaired (>−18%) in 53% of patients at baseline and T1, whereas only 13% showed persistent LV GLS reduction at T2. Follow-up CMR showed LGE persistence in 33.4% of cases. Conclusion: Early cardiac involvement significantly improves during follow-up of MIS-C patients. However, subclinical myocardial dysfunction seems to be still detectable after 6 months of follow-up in a not negligible proportion of them.